2021
DOI: 10.1093/eurheartj/ehab724.2835
|View full text |Cite
|
Sign up to set email alerts
|

Risks of trastuzumab-related cardiotoxicity in breast cancer patients in Taiwan

Abstract: Aims Despite being an essential therapy for breast cancer, trastuzumab has potential risks of cardiotoxicity. The incidence of trastuzumab-related major adverse cardiac and cerebrovascular event (MACCE) and its predictors remain unknown in Taiwan. Methods and results Through a three-hospital retrospective cohort study, we analyzed the incidence of MACCE in 386 breast cancer patients exposure to trastuzumab from 2010 to 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The result was consistent with the previous studies that trastuzumab was associated with increased heart failure incidence. Prior Taiwan NHIRDbased studies have also examined the potential confounding effects of anthracyclines on the cardiotoxicities [19,20]. Chang et al [19] found BC patients receiving trastuzumab had an increased risk of major adverse cardiac and cerebrovascular event (MACCE), especially HF, a similar but some different outcome endpoint compared to our current study.…”
Section: Discussionsupporting
confidence: 45%
“…The result was consistent with the previous studies that trastuzumab was associated with increased heart failure incidence. Prior Taiwan NHIRDbased studies have also examined the potential confounding effects of anthracyclines on the cardiotoxicities [19,20]. Chang et al [19] found BC patients receiving trastuzumab had an increased risk of major adverse cardiac and cerebrovascular event (MACCE), especially HF, a similar but some different outcome endpoint compared to our current study.…”
Section: Discussionsupporting
confidence: 45%